Variable structure position/force hybrid control of manipulators - Tenreiro Machado, J. A. (2019)
In this paper it is studied the implementation of a variable structure algorithm in the position/force hybrid control of robotic manipulators. The frequency response of the system is calculated and it is found to have good performances. An introduction to describing function analysis of the system is also included and effect of the controller sampling frequency is analysed.